Rediseño de una maquina inyectora de PET para la repotenciación de su funcionamiento en la empresa Bolten Ltda. de la ciudad de barranquilla (2021)
In this project, the redesign of the system of the injection unit of the FT 300 plastic injection machine will be carried out for the company BOLTEN LTDA. which is working at 33% efficiency due to the volumetric capacity of the machine. In the project, it will be carried out on the plastic injection process and the machines that carry out this process, the operation and its most important characteristics are investigated in order to carry out the design and later carry out the repowering of this. To develop the project, it was necessary to apply knowledge of hydraulic systems, automation, instrumentation and programming of logic controllers; to interpret the diagrams: electrical and hydraulic to facilitate preventive and corrective maintenance. A user manual was produced, and Bolten Ltda. Personnel were trained on the correct operation of the machine.